Identifikasi Senyawa Flavonoid Fraksi Etil Asetat Bunga Pacing Tawar (Costus speciosus) Metode FTIR sebagai Analgesik - Indri Maharani Syahputri; A.M.Muslihin; Ratih Arum Astuti (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Pain is a natural signal to tissue damage in the body. One of the plants that has the potential as a natural analgesic is the pacing tawar flower (Costus speciosus) which is known to contain compounds that play a role in providing analgesic effects. This research method uses a pre-post test design to see the effectiveness before and after being given a test suspension in the form of (mefenamic acid, Na CMC, and ethyl acetate fraction of pacing tawar flowers at doses of 125 mg/kgBB, 250 mg/kgBB, and 500 mg/kgBB) in mice induced by pain with the tail flick method. The results of the phytochemical screening study showed that only the ethyl acetate fraction of pacing tawar flowers (Costus speciosus) was positive for containing flavonoid compounds with the formation of a yellow color compared to the n-hexane fraction and the water fraction. Functional groups identified in flavonoid compounds are C-H, C=O, C-O groups. Ethyl acetate fraction of pacing tawar flower at doses of 250 mg/kgBB and 500 mg/kgBB can provide analgesic effects with a p value (<0.05). Based on the research that has been done, it can be concluded that the ethyl acetate fraction of pacing tawar flower contains flavonoid compounds that can inhibit pain with the most optimal and stable fraction dose at a dose fraction of 500 mg/kgBB with a p value (<0.05).